Pengembangan Media Animasi Fisika Menggunakan Software Adobe Flash Cs6 Pada Materi Momen Gaya - Putri Rahayu; Maria Dewati; Indica Yona Okyranida (UNIVERSITAS INDRAPRASTA PGRI, 2021)
In this study aims to find out the feasibility of physical animation media using adobe flash software Cs6 on material moment style. This research uses 4D research design consisting of 4 stages, namely Define, Design, Develop, and Disseminate. This research can only be completed in the development stage, this is due to the Covid 19 pandemic globally so researchers can not do the next research step. In this study using the instrument of initial needs observation sheet research and expert validation test questionnaire consisting of media experts and material experts. Based on the data of the results of research and discussion that has been described, it can be concluded that the Development of Animation Media Using Adobe Flash CS6 In the material of the style moment using the 4D model as the research is very feasible to use proven with the results of design validation conducted by means of validation tests media experts and material experts get results of 85 % and 80 % with very decent results and worth to use.